3D magnetic resonance velocimetry for the characterization of hydrodynamics in microdevices: Application to micromixers and comparison with CFD simulations. (5th April 2023) - Guerroudj, Feryal; Guendouz, Laouès; Hreiz, Rainier; Commenge, Jean-Marc; Bianchin, Jérémy; Morlot, Christophe; Dung Le, Tien; Perrin, Jean-Christophe
Highlights: An NMR instrumentation is developed to measure 3D velocity fields in microdevices. MRI measurements in an arrow-type micromixer are compared to CFD simulations. Small manufacturing defects strongly affect the flow and the mixing performance. Good agreement is obtained between numerical data and experimental measurements. Abstract: 3D velocity field measurements in an arrow-type micromixer are performed using nuclear magnetic resonance (NMR) imaging methods. A specific device has been set up including a home-made radiofrequency milli-coil matching the geometry of the manufactured micromixer, allowing an improvement of the signal-to-noise ratio by a factor 7 comparing to a standard commercial hardware. The NMR images obtained are compared to computational fluid dynamics (CFD) simulations. The very good agreement obtained between numerical data and experimental measurements revealed, on the one hand, the capacity of the developed method to perform a detailed and accurate study of phenomena occurring in a microstructured system and on the other hand, the great impact of small manufacturing defects on the hydrodynamics in a micromixer and thus on the mixing performances.